Professional Guidanceof the Teacher - ICTbasedapproach - Bezhina, V.V.; Solovyeva, N.A.; Utegenova, B.M. (“Shapak”,Kostanay, 2019)
The study manual based on interactive lectures is intended for students of pedagogical specialties studying the course "Professional guidance of the teacher" in English with the aim of forming a general idea about the nature and role of 7 Modules based Programme elaborated by NIS in the modern education system. This manual can be applied in high schools in the framework of the mainstream of the pedagogical cycle. The manual consists of an introduction, two sections: theoretical and practice-oriented blocks. In the theoretical part, the theoretical foundations of the core of the Programme in the pedagogical sphere are presented, the practical block represents the development of model guidance for the implementation of practical work, the tasks of the IWS and the other applied aspects of the Programme.